Genetic characterization of lagocephalus spadiceus among two populations using microsatellite dna markers - Tang, Janet Hung Sing (Universiti Malaysia Sarawak, UNIMAS, 2010)
This study was done to examine the efficacy of microsatellite primers developed from two puffer fishes (Takifugu rubripes and Takifugu obscures) through cross-species amplification in Lagocephalus spadiceus. Samples from 2 different geographical populations (1=Kudat & 2=Tawau) in the coastal area of Sabah were tested. PCR optimization was done to test a total of 20 primers from genus Takifugu and 6 primers were produced amplified products. They were subsequently used for screening in larger sample size. However, only one primer (P3) was successfully tested for polymorphism while the other five primers could not been tested due to shortage of chemicals for PCR. P3 primer produced low level of polymorphism when tested using 53 samples in both of the populations.